Taxonomic Validity of Dryopteris Laoshanensis J. X. LI ET S. T. Ma and Dryopteris Championii (Benth.) C. Chr. From China - Li, Xiao juan; Li, Jian xiu; Sun, Kang; Wang, Xiao (Bangladesh Journal of Botany, 2023)
A combination of plant taxonomy, micromorphological and palynological characters was used to systematically compare and study the status of the two closely related species, namely Dryopteris laoshanensis and D. championii. Results showed that the sporophylls of D. laoshanensis were triangularovate, with 1 alternate pair of pinnae at the base of the sporophylls, not shortened, and each alternate pair of pinnae gradually shortened upward; rhizome and petiole are densely covered with reddish brown ovatelanceolate scales; the sori are distantly placed from the main vein; spore perispore with curved ridges protrusions, which is clearly different from the D. championii. The leaves of D. championii were ovateoblong, 1 pair of pinnae at the base of the leaves slightly shortened, and the upper 2-4 pairs of pinnae were extended in sequence, which is the widest part of the leaves at the middle, and then the pinnae gradually shrinking upward; rhizome and petiole are densely covered with dark brown lanceolate scales; the sori close to main vein; spore perispore with tuberculiform and tuberculiform-rugulate protrusions. It provided micromorphological and palynological evidences for the clear identity of D. laoshanensis and D. championii as distinct species. Bangladesh J. Bot. 51(4): 863-871, 2022 (December) Special